ICT in reducing information asymmetry for financial sector competition - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2018)
In this study, we examine the role of information and communication technology in complementing information sharing bureaus (or private credit bureaus and public credit registries) for financial sector competition. Hitherto unexplored dimensions of financial sector competition are employed, namely: financial sector dynamics of formalization, informalization and non-formalization. The empirical evidence is based on 53 African countries for the period 2004-2011 and the Generalised Method of Moments (GMM) with forward orthogonal deviations. The findings differ across financial sectors in terms of marginal, net and threshold effects. By introducing the concept of financialization, the study unites two streams of research by: improving the macroeconomic literature on measuring financial development and responding to an evolving field of development literature by means of informal finance. Moreover, a practical method by which to disentangle the effects of reducing information asymmetry on various financial sectors is suggested. Policy implications are discussed.
Keywords: G20; G29; L96; O40; O55; 330; Information sharing; Banking competition; Africa